2022
DOI: 10.3389/fneur.2022.930635
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Susceptibility Vessel Sign in Patients With Malignancy-Related Acute Ischemic Stroke Treated With Mechanical Thrombectomy

Abstract: Background and PurposeClots rich in platelets and fibrin retrieved from patients with acute ischemic stroke (AIS) have been shown to be independently associated with the absence of the susceptibility vessel sign (SVS) on MRI and active malignancy. This study analyzed the association of SVS and the presence of active malignancy in patients with AIS who underwent mechanical thrombectomy (MT).MethodsThis single-center, retrospective, and cross-sectional study included consecutive patients with AIS with admission … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The use of oral anticoagulants seems more appropriate but major guidelines currently advocate for randomized trials ( 32 , 33 ). According to previous evidence, the absence of SVS demonstrated the strongest association with active cancer in multivariable analysis ( Figure 2 ) ( 14 ). Even if the auROC of the model with SVS tended to be greater, no statistical difference was found ( Figure 3A ).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The use of oral anticoagulants seems more appropriate but major guidelines currently advocate for randomized trials ( 32 , 33 ). According to previous evidence, the absence of SVS demonstrated the strongest association with active cancer in multivariable analysis ( Figure 2 ) ( 14 ). Even if the auROC of the model with SVS tended to be greater, no statistical difference was found ( Figure 3A ).…”
Section: Discussionsupporting
confidence: 66%
“…Newly diagnosed cancer within one year after the index stroke was defined as “occult cancer” at the time of stroke and considered an active cancer for the purposes of this study ( 4 , 20 , 21 ). As defined previously, patients with focal non-melanoma skin cancer and those treated with prophylactic hormone therapy for prior breast cancer were classified as not having active cancer ( 14 , 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Known cancer was considered active when being newly diagnosed, recurrent, or treated within 6 months before the index TIA, or in case of metastatic spread (according to information obtained from our clinic information system) ( 12 , 13 ). The limit of 12 months after TIA for the identification of occult cancer at the time of TIA was based on previous evidence ( 3 , 14 , 15 ). Occult cancer cases were either retrospectively identified in our clinic information system or documented in follow-up consultations.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study by Beyeler et al on 40 AIS patients with cancer found that the absence of SVS was associated with having a cancer but could not predict occult cancer better than clinical predictors. 100 A more refined SVS analysis using quantitative susceptibility mapping may increase the predictive power of this model. 101 As described previously (see "Stroke Mechanisms in Cancer Patients"), NBTE is another possible mechanism of cancer-related stroke linked to hypercoagulability.…”
Section: Magnetic Resonance Imaging and Transcranial Dopplermentioning
confidence: 99%